Vessel-wall MRI in thunderclap headache: A useful tool to answer the riddle?. Issue 2 (April 2021) - Rustici, Arianna; Merli, Elena; Cevoli, Sabina; Donato, Marco Di; Pierangeli, Giulia; Favoni, Valentina; Bortolotti, Carlo; Sturiale, Carmelo; Cortelli, Pietro; Cirillo, Luigi
Background: Finding an intracranial aneurysm (IA) during a thunderclap headache (TCH) attack, represents a problem because it is necessary to distinguish whether the aneurysm is responsible for the headache as a warning leak or as an incidental finding. High-Resolution Vessel-Wall (HRVW) MRI sequences have been proposed to assess the stability of the wall, as it permits to detect the presence of aneurysmal wall enhancement (AWE). In fact, AWE has been confirmed due to inflammation, recognizable preceding rupture. Case 1: A 37-year-old woman with a migraine more intense than her usual. A CTA revealed a 10 mm AComA aneurysm without subarachnoid hemorrhage (SAH) and HRVW-MRI excluded AWE. The patient's headache improved, and therefore, the aneurysm was considered an incidental finding, and the headache diagnosed as TCH attack. Subsequently, the aneurysm was surgically clipped, and typical migraine relapsed was reported at follow-up (FU). Case 2: A 67-year-old woman with no history of headaches underwent CTA for an abrupt onset of headache. A 7 mm right carotid-ophthalmic aneurysm with no sign of SAH was discovered. HRVW-MRI demonstrated AWE and thus, a TCH attack for a warning leak of an unstable wall was suspected. Endovascular coiling was immediately performed and at FU any further headache attack was reported. Conclusions: HRVW-MRI is useful in case of finding aneurysm as the cause of headaches, particularly the TCH attack. In fact, HRVW-MRI could assess the stability of the aneurysms wall, allowing different patient management and eventually the aneurysmal treatment.